Response of Growth and Production of Sweet Potato (Ipomea Batatas L.) Due to The Application of TSP Fertilizer and Cow Manure - Wahyunita Sitinjak (Postgraduate, University of Mataram, 2025)
The purpose of this study was to determine the response of growth and production of sweet potatoes (Ipomea batatas L.) due to the application of TSP fertilizer and cow manure, carried out in Huta I Silau Bayu, Gunung Maligas District, Simalungun Regency, North Sumatra, from May to August 2024. The study used a factorial Randomized Block Design (RAK), with 2 factors. The first factor is TSP fertilizer with 4 levels, namely P1 = 20.4g / plot, P2 = 40.8g / plot, P3 = 61.2g / plot, P4 = 81.6g / plot. The second factor is Cow Manure with 4 levels, namely: S0 = No Treatment, S1 = 5.1kg / plot, S2 = 10.2kg / plot, S3 = 15.3kg / plot. Observed parameters were Tendrils Length (cm) at 3 and 5 MST, Number of Bulbs Per Plant (fruit), Number of Bulbs Per Plot (bulbs), Bulb Weight Per Plant (g) and Bulb Weight Per Plot (kg). The results showed that TSP fertilizer application significantly affected Tendrils Length (cm) at 3 and 5 MST, Number of Bulbs Per Plant (bulbs), Number of Bulbs Per Plot (bulbs), Bulb Weight Per Plant (g) and Bulb Weight Per Plot (kg). The best dose of TSP fertilizer was found in the treatment of 30 tons/ha: 15.3 kg/plot. Cow Manure treatment significantly affected Tendrils Length (cm) at 3 and 5 MST, Number of Bulbs Per Plant (bulbs), Number of Bulbs Per Plot (bulbs), Bulb Weight Per Plant (g) and Bulb Weight Per Plot (kg). The best dose of cow manure was found in the treatment of 160 kg/ha: 81.6 g/plot. The interaction treatment of TSP fertilizer and Cow Manure fertilizer significantly affected the Length of Tendrils (cm) at the age of 3 and 5 MST, Number of Bulbs Per Plant (bulbs), Number of Bulbs Per Plot (bulbs), and Bulb Weight Per Plot (kg). It had no significant effect on Bulb Weight Per Plant (g). The best interaction treatment was in the TSP treatment (30 tons/ha: 15.3 kg/plot) with cow manure (160 kg/ha: 81.6 g/plot).